2017
DOI: 10.1039/c7cp00857k
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of dopant ions around poly(3,4-ethylenedioxythiophene) chains: a theoretical study

Abstract: The effect of counterions and multiple polymer chains on the properties and structure of poly(3,4-ethylenedioxythiophene) (PEDOT) doped with ClO has been examined using density functional theory (DFT) calculations with periodic boundary conditions (PBCs). Calculations on a one-dimensional periodic model with four explicit polymer repeat units and two ClO molecules indicate that the latter are separated as much as possible, with the salt structure and band gap obtained from such ClO distribution being in excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…Nevertheless, the obtained inter-chain S•••S distances are significantly lower than those previously reported from 1D-PBC DFT calculations on PEDOT doped with ClO 4 ions (d = 5.89 Å). [30] Thus, the present study indicates that compaction effect is larger than reported in previous works. PEDOT models, while Fig.…”
Section: Supercellsupporting
confidence: 53%
See 2 more Smart Citations
“…Nevertheless, the obtained inter-chain S•••S distances are significantly lower than those previously reported from 1D-PBC DFT calculations on PEDOT doped with ClO 4 ions (d = 5.89 Å). [30] Thus, the present study indicates that compaction effect is larger than reported in previous works. PEDOT models, while Fig.…”
Section: Supercellsupporting
confidence: 53%
“…Initial coordinates were obtained from a previous crystallographic study using 1D-PBC approach. [30] The other four systems were used to model PEDOT surfaces, which were build starting from the previous optimized bulk system but adding a vacuum region of 45 Å along lattice vector b. In this case, two of the models simulated the raw surface while the other two simulated the porous nanomembrane.…”
Section: Chemical Characterization Of Oxidized-reduced Pedot/p Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the borders C α C β double bond characters are greater and have higher order indexes, indicating that the π conjugation is less present. 16,30 This parameter indicates that the EDOT 16 is a suitable model to represent the PEDOT polymeric chains. EDOT 16 oligomer model was used for calculation of vibrational modes of PEDOT polymer, but the absence of resonance effects precludes the use of its theoretical Raman spectra for analysing relative intensities of the experimental bands.…”
Section: Density Functional Theory Calculationsmentioning
confidence: 99%
“…In earlier theoretical work doped PEDOT with tosylate or other counterions was analyzed using density functional theory (DFT) assuming perfect infinite crystalline order. [28][29][30] Recent All Atomistic (AA) Molecular Dynamics (MD) calculations for PEDOT doped with different molecular counterions (including Tos) reveal a complex morphology where small crystallites consisting of several p-p stacking PEDOT chains are embedded in a polymer matrix including PEDOT chains, Tos counterions and water molecules. 16,31 Because of computational limitations, AA MD simulations do not always allow one to reach a lengthscale needed to study the morphology of a realistic material.…”
Section: Introductionmentioning
confidence: 99%